Pengalaman Konsumen mengenai Layanan Huling (Haus Keliling) di Jakarta - Nurhaliza, Nabilah; Ayuna, Kania Anindya; Rachmawati, Dewi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze consumer experiences with the Huling (Haus Keliling) service in Jakarta using Schmitt’s (1999) experiential marketing framework. Studies that specifically examine multi-variant mobile beverage services based on e-bikes through the lens of the five dimensions of experiential marketing are still rare, and this research aims to address this gap in the literature. The research adopts a qualitative phenomenological approach through in-depth interviews and observations of consumers selected via accidental sampling. Findings reveal that all five experiential dimensions, namely sense, feel, think, act, and relate are present in Huling’s service. Visual elements and taste provide strong sensory appeal, while emotional connection and product consistency require improvement. The study concludes that Huling offers a consumption experience that is not only functional and practical but also shapes consumer perception, emotional engagement, and social connection. Strategic recommendations include enhancing emotional storytelling, ensuring consistent taste quality, and developing digital features such as cart tracking and loyalty programs to strengthen consumer attachment and competitive advantage.